2014
DOI: 10.1111/hae.12436
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors influencing inhibitor development in a cohort of South African haemophilia A patients

Abstract: A critical complication of factor VIII (FVIII) replacement therapy in Haemophilia A (HA) treatment is inhibitor development. Known genetic factors predisposing to inhibitor development include FVIII (F8) gene mutations, ethnicity, a family history of inhibitors and FVIII haplotype mismatch. The aim of this study was to characterize and correlate these genetic factors in a cohort of South African HA patients. This was a retrospective study that included 229 patients and involved the analysis of patient files, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 22 publications
1
25
1
2
Order By: Relevance
“…14 Subsequent studies have not shown a statistical link between F8 polymorphisms and inhibitor incidence. [27][28][29] The present study focuses primarily on inhibitor incidence in patients with severe HA. Seven subjects who had an intron-22 inversion mutation but baseline clotting activity $1% normal were also included, as they are not expected to circulate FVIII.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Subsequent studies have not shown a statistical link between F8 polymorphisms and inhibitor incidence. [27][28][29] The present study focuses primarily on inhibitor incidence in patients with severe HA. Seven subjects who had an intron-22 inversion mutation but baseline clotting activity $1% normal were also included, as they are not expected to circulate FVIII.…”
Section: Discussionmentioning
confidence: 99%
“…28 Multiple-exon deletions have been shown to carry the largest inhibitor risk for patients with severe HA, whereas missense mutations and small insertions/deletions carry lower risks. 2 The race-associated inhibitor risks associated with these types of mutations could not be determined because the subgroups in this study were too small.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, this approach has been applied to understand genetic basis of immunogenicity to recombinant Factor VIII, a BT used for treatment of hemophilia A (66)(67)(68)(69)(70). A growing body of literature points to influence of human genetic variability on efficacy as well as tolerability/ adverse effects of a number of vaccines (reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…4 Subsequent studies of small populations of patients of African ancestry have failed to confirm this finding. 57 The haplotypes investigated are rare in White populations, and no correlation with inhibitors was found in substantially sized groups of White patients. 5, 8 …”
mentioning
confidence: 87%